Women and the metabolic syndrome: an overview of its peculiarities - Allende, Myriam (Puerto Rico Health Sciences Journal, 2008)
Objective: the peculiarities of the Metabolic Syndrome in women regarding frequency, pathophysiology, manifestations and therapy will be analyzed. recommendations will be given for prevention of metabolic syndrome and possible reduction of risks factors for cardiovascular disease. Methods: a review of pertinent studies serves as the basis for the analysis and recommendations of therapeutic strategies in women with metabolic syndrome. Results: Metabolic syndrome, a conglomerate of obesity, hypertension, hyperglycemia, low high density cholesterol and elevated triglycerides can be found frequently in women, especially with polycystic ovaries or in the post-menopausal period. Insulin resistance and its metabolic consequences can lead to an increased risk of cardiovascular disease. There are interventions that can reduce insulin resistance and the other components which may lessen this risk in women with the metabolic syndrome. Conclusion: this article summarizes the peculiarities of the metabolic syndrome in women, especially with polycystic ovaries or at postmenopause. evidencebased medicine is reviewed and used together with the recommendations for therapy and for the prevention of cardiovascular disease in women with this condition.